Neighbourhood Gangs, Crime Spillovers, and Teenage Motherhood - Christian Dustmann; Mikkel Mertz; Anna Okatenko (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
Using an identification strategy based on random assignment of refugees to different municipalities in Denmark between 1986 and 1998, we find strong evidence that gang crime rates in the neighbourhood at assignment increase the probability of boys to commit crimes before the age of 19, and that gang crime (but not other crime) increases the likelihood of teenage motherhood for girls. Higher levels of gang crime also have detrimental and long-lasting effects, with men experiencing significantly higher levels of inactivity and women experiencing lower earnings and higher levels of welfare benefit claims at ages 19 to 28.
Keywords: J1; K4; I3; 330; Crime spillovers; gang crime; teenage motherhood